Blockchain para rastreabilidade e controle de qualidade de componentes eletrônicos: estudo de caso em uma empresa do setor eletrônico em Manaus - Sequeira, Leandro Sérgio Amaral (Brasil, 2024)
This study extensively investigated the implementation and impacts of advanced traceability and Blockchain technologies at Delta Company, situated in the Industrial District of Manaus. The research focused on how these technologies were deployed to enhance operational management and bolster quality control across the production chain. Employing methodologies such as workflow analysis, performance charts, and comparative tables, the study examined the effects of these innovations on reducing rework, improving operational efficiency, and enhancing customer satisfaction. The findings demonstrated a significant decrease in rework rates, underscoring substantial improvements in the reliability and consistency of products delivered to customers.